PHYTOCHEMICAL COMPOSITION, ANTIOXIDANT, ANTIMICROBIAL AND ANTIGLYCATION EFFICACY OF SYZYGIUM CUMINI - Muhammad Waqas; Beenish Akram; Tahseen Ghous; Mukhtar Ahmed (Journal of Animal and Plant Sciences, 2023)
Syzygium cumini, a medicinal plant of Myrtaceae family, has worldwide presence. Previous literature has pointed out importance of this plant from medicinal point of view. This plant has shown its potential against bacteria, fungus, spleen enlargement, urinary infections, cancer and fever. The present work was designed to examine different therapeutic effects of its extracts. Aqueous macerated and decocted extracts of leaf, fresh fruit, dry fruit, fresh seed, dry seed, and bark were prepared for in-vitro analytical purposes. Phytochemical screening was done by qualitative and quantitative methods. Antiradical efficacy was assessed by DPPH (1, 1-diphenyl-2-picrylhydrazyl), ABTS (2, 2-azinobis-(3-ethylbenzothiazoline-6-sulphonic acid) and metal chelation assays. Glycation inhibitory potential was examined by spectrophotometric and spectrofluorometric methods. Disc diffusion method was adopted to analyze antimicrobial activity. Phytochemical screening confirmed significant presence of tannins, saponins, terpenoids, cardiac glycosides, flavonoids, phenols and carbohydrates. Total phenolic contents (TPC) and total flavonoid contents (TFC) were shown as gallic acid and rutin equivalents respectively. Maximum presence of TPC was found in decocted dry seed extract (0.603±0.001mg/g) and maximum TFC were estimated in decocted leaf extract (0.09±0.012 mg/g). Decocted and macerated fresh fruit extracts showed best ability to reduce DPPH (93.1±0.6 % and 91.3±0.2 % respectively). Macerated fresh seed extract and decocted bark extract exhibited maximum antiradical potential (85.7±1.2 % and 84.3±0.8 % respectively) in ABTS assay. In metal chelation assay maximum radical Inhibition potential was observed for macerated bark extract (91.4±0.6 %) and decocted fresh seed extract (91.6±1.1 %). Against all studied microbial strains (Escherichia coli, Staphylococcus aureus, Bacillus subtilis, Pseudomonas aeruginosa) highest inhibition zones were given by bark extract. Bark and dry seed extracts showed 86% and 88% glycation inhibition potential in spectrophotometric and spectrofluorometric analysis respectively. It is concluded that all parts of this plant possess antiradical, antimicrobial and glycation inhibition potential. So, this plant can be used to cure many diseases.
Keywords: Metal Chelating Activity; Advanced Glycation End Products; Secondary Metabolites; Fluorescence; Polyphenols